2020
DOI: 10.1101/2020.05.21.108746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilizing Temporal Measurements from UAVs to Assess Root Lodging in Maize and its Impact on Productivity

Abstract: 1 2 Both stalk and root lodging can cause significant yield losses in maize; however, maize plants 3 are often able to recover from root lodging. There is potential among breeding programs for 4 developing lines that are more tolerant and can more rapidly recover from root lodging. We 5 assessed the incidence of root lodging utilizing end-of-season lodging scores collected among 6 the Genomes 2 Fields (G2F) initiative trials and found a large yet variable incidence of lodging 7 across states, years, and genoty… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In maize, lodging has been shown to reduce yield by 3%-25% (Carter & Hudelson, 1988;Flint-Garcia et al, 2003;Tirado et al, 2020). For stalk lodging, biomechanical measures of stalk breaking strength and stalk flexural stiffness have shown high association with lodging-resistance (Robertson et al, 2016;Sekhon et al, 2020).…”
mentioning
confidence: 99%
“…In maize, lodging has been shown to reduce yield by 3%-25% (Carter & Hudelson, 1988;Flint-Garcia et al, 2003;Tirado et al, 2020). For stalk lodging, biomechanical measures of stalk breaking strength and stalk flexural stiffness have shown high association with lodging-resistance (Robertson et al, 2016;Sekhon et al, 2020).…”
mentioning
confidence: 99%
“…A failure of root anchorage, referred to as root lodging, has detrimental impacts on maize production (Hostetler et al, 2022b; Tirado et al, 2021). We have previously shown that brace root phenotypes (from the roots that enter the soil) can predict the brace root contribution to anchorage and lodging susceptibility (Hostetler et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…The different origins and destinations of these roots result in different contributions to root functions such as mechanical support, important for lodging resistance, and nutrient supply, required for growth and development. A failure of root anchorage, referred to as root lodging, has detrimental impacts on maize production (Hostetler et al, 2022b;Tirado et al, 2021). We have previously shown that brace root phenotypes (from the roots that enter the soil) can predict the brace root contribution to anchorage and lodging susceptibility (Hostetler et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Crop failure from mechanical stress is called lodging and is defined as the displacement of plants from vertical (Rajkumara, 2008). In maize, lodging is reported to cause between 7-25% yield loss (Carter and Hudelson, 1988; Flint-Garcia et al, 2003; Tirado et al, 2020) and can be attributed to stalk and/or root failure (Berry et al, 2004; Rajkumara, 2008). Stalk lodging occurs at late growth stages when internodes buckle below the ear, whereas root lodging can occur at any growth stage when the root system fails by uprooting and/or breaking (Berry et al, 2004; Rajkumara, 2008; Erndwein et al, 2020; Hostetler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%